POLA PEMBINAAN BACA TULIS AL-QUR’AN MAHASISWA PAI FAKULTAS FITK UIN RADEN FATAH PALEMBANG - Baldi Anggara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
The background of the selection of this title is based on empirical and theoretical studies, that the development of the Al-Qur'an reading and writing of the students should properly be considered. Based on preliminary observations, some of the students in the PAI study program in the ability to read Al-Qur'an were considered not able to read the Koran properly and correctly because when the new student entrance examination selection did not have the Al-Qur'an reading test. And when getting the Tahsinul Qiroah course also done by educators is not maximal. This can be seen from the results of an interview with one of the instructors, saying that 25 students had not been fluent in reading the Qur'an even 15 people had not been able to read the Koran properly. Supported also by looking at the documentation of the results of the Tahsinul Qiroah course (Student's Al-Qur'an Writing) there are still many who are below the average score. This research is motivated by a problem, namely first, what is the pattern of Al-Qur'an reading and writing for students of PAI FITK UIN Raden Fatah Palembang Study Program; Second, what are the results of the Al-Qur'an reading and writing coaching for students of PAI FITK UIN Raden Fatah Palembang; and Third, what factors influence the implementation of Al-Qur'an reading and writing for students of PAI Study Program at FITK UIN Raden Fatah Palembang. The research method used is descriptive qualitative. Qualitative descriptive research aims to increase the facts, circumstances and phenomena that occur when research takes place and present data as is. The location of the study was Student of PAI FITK UIN Raden Fatah Palembang.